TPM a route to world-class performance - Willmott, Peter; McCarthy, Dennis (Oxford ; Boston : Butterworth-Heinemann, 2001)
Total productive maintenance (TPM), a Japanese management protocol developed to alleviate production losses caused by machine breakdowns has moved on. Through TPM, more companies accept the concept of Zero Breakdowns as achievable. From the foundation of zero breakdowns, world class plants are able to run for complete shifts without the need for intervention. TPM is still pushing back the boundaries of what was thought possible. Driven by the proven principles of TPM, the book emphasises the need to build on existing good practices and to win commitment by delivering results. The book provides a practical guide to delivering TPM benefits and is based on the authors' first hand experience of seeing TPM in Japan. It adapts these benefits to suit the strategic needs of companies across four continents. "TPM A Route to World Class Performance" builds on Peter Willmott's earlier book, "TPM the Western Way", updating the scope of applications and tools. The TPM route map is updated to include the journey to zero breakdowns and beyond. It also provides a systematic structure to evolve from the classic Total Productive Maintenance towards Total Productive Manufacturing and deliver a Totally Productive Operation capable of world leading performance.
Putting TPM into perspective from Total Productive Maintenance to Total Productive Manufacturing; Assessing the true costs and benefits of TPM; The top-down and bottom-up realities of TPM; Techniques to Deliver TPM principles; The TPM Improvement Plan; Applying the TPM improvement plan; Planning and launching the TPM pilot; Managing the TPM journey; TPM for equipment designers and suppliers; TPM in Administration; Case Studies.
Includes index.
Keywords: Total productive maintenance; Plant maintenance -- Quality control; Electronic books